Evaluasi Formatif Program Rumah Pintar Pemilu: Pembelajaran Dari KPU Bengkulu 2018-2023 - Septianda Hendarno , Dimas; Yogopriyatno, Jatmiko (Faculty of Social and Political Science, 2024)
This research aims to describe the Evaluation of the Election Smart House Program in terms of program objectives and outcomes, namely output and outcome. The research method used is a qualitative descriptive research method. Data collection techniques in this research are observation, interviews, and, documentation. The data analysis techniques used in this research are data reduction, data presentation, and conclusion. The research aspect was adopted from Wayne Parsons' evaluation theory which consists of two factors, namely output and outcome. The results of research conducted by the author show that the Election Smart House Program is not optimal due to 1). Bengkulu people who are reluctant to participate in elections can increase participation and increase public knowledge regarding elections and democracy. 2). Several activities have not been carried out well. 3) only a few activity programs have been implemented so the impact felt by the community is not yet optimal. So the author recommends that the smart home election program in the following year be implemented well and recruit cadres so that there is no shortage of human resources in carrying out smart home election activities.